Compatibility-tuned distribution of nanoparticles in co-continuous rubber structures toward microwave absorption enhancement. Issue 2 (4th January 2017) - Li, Lefan; Zhao, Pengfei; Luo, Yongyue; Yu, Heping; Tao, Jinlong; He, Dongning; Gong, Wei; Li, Dejun; Wang, Zhifen; Peng, Zheng
Abstract : Carbon black incorporated natural rubber/epoxidized natural rubber composites with enhanced microwave absorption capacity have been designed by a novel approach of compatibility-tuned nanoparticles distribution in co-continuous rubber blends. Abstract : Development of novel and versatile approaches to engineer composites with light density, broad effective bandwidth and high microwave absorption (MA) capacity is of great importance. Here, co-continuous natural rubber/epoxidized natural rubber (NR/ENR) blends with a selective distribution of conductive carbon black nanoparticles (CCBs), have been fabricated by tow-roll mixing. ENR with abundant epoxide groups shows inferior wettability to CCB than NR, which is responsible for the preferential location of CCB in the NR/ENR blend. Increasing the epoxidation level of ENR promotes the preferential location of CCB and creates stronger dielectric loss, thus enhancing the MA properties of CCB/NR/ENR composites. When the epoxidation level increases to 40 mol%, the MA capacity of the composite has been significantly enhanced by 40%. Meanwhile, the qualified frequency bandwidth (RL < −10 dB) of composites with ENR is 85% broader than that of CCB/NR composites. Such a novel approach of compatibility-tuned nanoparticles distribution in co-continuous rubber blends will significantly promote the multi-functional use of rubber and carbonaceous resources.